2021
DOI: 10.1126/sciadv.abj8080
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive receptors in neural stem cells link stress-induced hyperthermia to impaired neurogenesis via microglial engulfment

Abstract: Hyperthermia mediates social defeat stress–induced impairment of adult neurogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The neural progenitor cells are majorly found in the subventricular zone and hippocampus, and they are also found in other brain regions including hypothalamus, substantia nigra, and striatum (Jurkowski et al, 2020). A recent study reported impaired neurogenesis in the mice exposed to social defeat stress-induced hyperthermia (Hoshi et al, 2021). Previously, neural progenitor cells were reported to migrate from subventricular zone to corpus callosum upon damage (Mallett et al, 2018;Nait-Oumesmar et al, 1999) and under normal conditions (Sohn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The neural progenitor cells are majorly found in the subventricular zone and hippocampus, and they are also found in other brain regions including hypothalamus, substantia nigra, and striatum (Jurkowski et al, 2020). A recent study reported impaired neurogenesis in the mice exposed to social defeat stress-induced hyperthermia (Hoshi et al, 2021). Previously, neural progenitor cells were reported to migrate from subventricular zone to corpus callosum upon damage (Mallett et al, 2018;Nait-Oumesmar et al, 1999) and under normal conditions (Sohn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, miR-146a-5p decreased the expression of important regulators of neurogenesis, including krüppel-like factor 4 and cyclin-dependent kinase-like 5, reducing neurogenesis and inducing depressive-like behavior thereafter [58]. Another recent study highlighted how microglial phagocytosis alters neurogenesis in the CSDS model [59]. Phosphatidylserine (PS)-expressing NSCs were found in the DG; NSCs express thermosensitive transient receptor potential vanilloid 4 (TRPV4), which was activated by CSDS.…”
Section: Role Of Microglial Inflammatory Signaling In the Pathology O...mentioning
confidence: 99%
“…The hippocampal sections were incubated in PBS, 0.3% Triton X-100, and 10% goat serum at room temperature for 30 min and washed with PBS. The tissues were subjected to the Click-iT reaction (Thermo Fisher Scienti c) to uorescently visualize EdU-labeled cells with Alexa Fluor 594 for detection 42 and washed with PBS, followed by counterstaining with NeuroTrace 435/455 blue uorescent Nissl stain (1:500, N21479, Thermo Fisher Scienti c) in PBS (containing Triton X-100) for 1.5 h at room temperature.…”
Section: Edu Labelingmentioning
confidence: 99%